TOLERANSI HUKUM ISLAM DALAM PIDANA - Shafra, Shafra (Alhurriyah, 2009)
This article attempts to reflect towards the Islamic criminal law (jinayat) as a humanism law and as humanitarianism in this life. Regarding to the death sentence and hand cut sentence for instance, many orientalists have misinterpreted that the Islamic criminal law has been regarded as a cruel law without any tolerant. According to them, there is no any tolerant in the Islamic criminal law at all. Whereas, this kind of view is absolutely wrong. In the case of the Islamic criminal law, there still has any tolerance. But not all kind of tolerance in the Islamic criminal law could be applied in every case. The tolerance could be applied in the killing case only, this is caused that the killing case involves his individual rights and not regarded as God’s rights. Specifically, there is a tolerance space related with this problem. So that, the cast could get any tolerance for his punishment, it does not mean that he would not get any punishment at all. Finally, this article aims to minimize the wrong view without any revision towards the general or universal subsection law.